Potensi Pasar Pembiayaan KMF Purna BRISyariah iB Dengan Akad Murabahah (Pendekatan Analisis SWOT) - Soekapdjo, Soeharjoto; Dewi, Agnes Panca (www.bsi.ac.id, 2021)
Banks and other financial institutions open majority the market to the productive age community but BRISyariah iB focus on retiree. Purpose of this research is to determine market potential of KMF Purna financing with the Murabahah contract at BRISyariah iB. SWOT analysis is used as a method in this research. Result shown, that this financing has a mechanism that well structured and in accordance with the provisions of the OJK which deals with Islamic banking, to avoid misunderstandings that can harm and reduce the trust of both parties. Result of KMF Purna with the Murabahah contract financing at BRISyariah iB having a great potential market because focus on retiree market share who need financial assistance for goods and services fulfillment as well as their customers at an late adulthood who want a sense of security. For this reason, BRISyariah iB in financing KMF Purna with the Murababah agreement can optimize the market by increasing human resources, digital technology, marketing, and collaboration with other companies in order to increase competitiveness with other financing institutions.